The optimal enforcement of antitrust law - Michele Polo (Fondazione Eni Enrico Mattei (FEEM), 1997)
This paper analyses the optimal enforcement of competition policy against collusion under asymmetric information on cartel's costs and observable prices. The implementable price schedules are increasing, and the net profits decreasing, in cartel's costs, while expected penalties are increasing in observed prices. Hence, more efficient cartels enjoy positive (informational) rents. The optimal price schedule is higher than marginal costs even when enforcement is costless: since penalties can be at best zero, informational rents for more efficient types must be created through price-cost margins. This allocative distortion is lower for more efficient types, while full collusion can be tolerated for high cost cartels. Costly enforcement tends to reduce this distortion for less efficient types. Comparing antitrust enforcement with regulation, we find that regulation with positive transfers is better than antitrust enforcement, which however allows to implement more efficient outcomes than regulations without transfers.
Keywords: 330; Kartellrecht; Preisregulierung; Asymmetrische Information; Theorie